البُعْد اللغوي في مقاصد الشريعة الإسلامية: Linguistic Dimension in the Purposes of Islamic law - الموقت حمادي (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2013)
يتأسّس البحث في "البُعْد اللغوي في مقاصد الشريعة الإسلامية" على قضية معرفية، يراهن من خلالها التدليل على وجود علاقة طبيعية تربط اللغة بالمقصد الشرعي، اعتباراً للمنحى الذي يشتغل عليه، ومن أجله ذلك المقصد، في تبيين مصالح الفرد وحفظ كلّياته. فاللغة أصل منهجي حاكم على قضايا الفهم والتأويل للنصّ القرآني أو النبوي، لا مادة معرفية فحسب؛ والممارسة الفقهية والاجتهادية الجليلة لا تُبنى إلا على الممارسة اللغوية السليمة التي دعا إليها القرآن في غير ما موضع من آيه. لذا، كان فهم المقول يُبنى على فهم القول، وفهم القول لا يُطاوِعُ صاحبه إلا باللغة، ومعرفة كافية بفقهها وأسرارها. The study of "linguistic dimension in the purposes of Islamic law" is an epistemological issue through which it seeks to demonstrate the existence of a natural relationship between language and legitimate purpose for which the language is used; i.e., demonstrating the individual’s interests and maintaining his or her overall requisites. Language is a methodological foundation for determining human understanding and interpretation of the text of the Qur'an or the Sunnah, and not simply a cognitive matter. The jurisprudential practice is based specifically on the proper linguistic practice required by the Qur’an in many places. The understanding of what is being said, therefore, should be built on understanding of what should be said, and this is dependent on the language and sufficient knowledge of its secrets.